Integrated Approach of Dam Break Analysis and Flood Inundation Mapping Using HEC-RASA Case Study of Ukai Dam, India - Pathan A.I.; Mohapatra P.K.; Shaikh A.A.; Agnihotri P.G.; Sidek L.M.; Ibrahim M. (Springer Science and Business Media Deutschland GmbH, 2024)
Dam safety risks towards human communities have increased substantially in recent decades. They are the result of dam safety issues leading to failure, which have been aggravated by large losses in downstream areas due to increased inhabitants and settlement. It is critical for carrying out dam break studies to conduct an impact assessment of the dam failure as well as provide information on potential flood inundation. A 2D HEC-RAS hydrodynamic model is developed in the present study to examine the flood wave caused by the speculative failure of Ukai Dam and examine outflow and possible inundation extents along downstream areas of Lower Tapi Basin. Topography and elevation data of the basin is obtained from a 30-m resolution SRTM digital elevation model. To conduct the dam break analysis, the inflow hydrograph during 2006 flood event is considered for upstream boundary condition and the downstream boundary condition is defined by normal depth. The outflow hydrograph due to the failure event has the ability to deluge the downstream region of the dam. The dam-break outflow hydrograph indicated the peak flow of 127,682 m3/s at the dam and 46,591 m3/s at the downstream end of the river. The proposed model proves to be an efficient tool for the stakeholders to investigate the flood depth, velocity, arrival time of flood at different spots, and inundation boundary for dam failure event in advance. Moreover, the study can provide valuable information for local authorities for planning effective dam safety measures to mitigate the effects of flood. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.